Estudio de la responsabilidad social de las empresas: Aplicaciones a las empresas de Gran Canaria - José Boza Chirino; Daniel Pérez Estevez (Colegio de Economistas de A Coru\~na, 2009)
– Corporate Social Responsability is one of the strongest bets for the future in the European Union. CSR principles are characterised by the willingness to incorporate a series of management guidelines to achieve positive actions (ethical, solidarity, environmental, ...) within the interest groups. In order to measure the perception which both businessmen and consumers from Gran Canaria have on CSR, we have compilated information by ellaborating surveys. Statistical exploitation shows that, even when the perception differs within everyone of them, they are too optimist when they believe they are acting under CSR criteria.
Keywords: 330; corporate social responsability; perceptions managers vs consumers; Corporate Social Responsibility; Gran Canaria